Irisin Protects Against Motor Dysfunction of Rats with Spinal Cord Injury via Adenosine 5'-Monophosphate (AMP)-Activated Protein Kinase-Nuclear Factor Kappa-B Pathway - Jiang, Xi; Shen, Zhihong; Chen, Jin; Wang, Chao; Gao, Zhan; Yu, Songling; Yu, Xuefeng; Chen, Lei; Xu, Lexing; Chen, Ziwei; Ni, Wenjuan (Frontiers in Pharmacology, 2020)
The aim of the present research was to investigate the effects of irisin, a skeletal muscle-derived myokine, on spinal cord injury (SCI) in rats and explore the possible mechanisms. SCI model was constructed in male SD rats. The effects of irisin on SCI rats were assessed via behavior tests including Basso, Beattie, and Bresnahan (BBB) scoring method and inclined plane test, followed by histomorphology tests including Haematoxylin-Eosin (HE) staining, Nissl staining, and transmission electron microscope examination. Biochemical analyses including polymerase chain reaction (PCR), Western blots and enzyme linked immunosorbent assay (ELISA) were employed to further evaluate the changes at molecular level of SCI rats. In addition, lipopolysaccharide (LPS)-induced cell damage model was established in PC12 cells to verify the mechanism of irisin’s effect on nerve cells in vitro. Results showed that the BBB score and the angle of incline significantly decreased after SCI surgery, however, chronic irisin treatment improved SCI-induced motor dysfunction. HE and Nissl staining assays showed that SCI surgery induced histological injury of spinal cord, which could be reversed by irisin treatment. Morphological abnormality of nerve cells caused by SCI also could be alleviated by irisin. Further biochemical analyses showed that irisin inhibited SCI-induced overexpression of IL-1β, IL-6, TNF-α[inducible nitricoxidesynthase (iNOS) and Cyclooxygenase-2 (COX-2)], as well as NF-κBp65 in rats, and the positive function of irisin could be reversed by Compound C treatment. In our in vitro study, LPS-induced declines of cell viability and neurite length of PC12 cell were inhibited by irisin treatment, and irisin inhibited LPS-induced overexpression of NF-κBp65, IL-1β, IL-6, TNF-α, iNOS and COX-2. These changes could be reversed by AMPK siRNA pre-treatment. Taken together, irisin could protect the rats from spinal cord injury, and its protection is associated with the regulation of adenosine monophosphate-activated protein kinase (AMPK)- nuclear factor kappa-B (NF-κB) signaling pathway.